Evaluation of rice gluten meal as a potential alternate feed source for poultry - ADIL, S; A WANI, MANZOOR; K TYAGI, PROMOD; MANDAL, A B (The Indian Journal of Animal Sciences, 2022)
A biological experiment was conducted in a factorial design (3×2×2) involving two substitution levels (20 and 40%) of basal diet with rice gluten meal (RGM) with and without enzymes (protease and multi-enzyme) in cockerels following practical diet replacement method. Birds (72) were divided into nine groups containing eight cockerel birds each. The conventional grower ration was provided to the birds for an adaptation period of 10 days followed by feeding of experimental diets for 14 days with final four days as collection period. A metabolic trial lasting for four days was done in which weighed quantity of feed was offered to birds and faeces voided were collected, weighed and dried. Both feed and faeces were analysed for gross energy value to calculate the apparent metabolizable energy for all diets and then apparent metabolizable energy (AME) of test ingredient, i.e. rice gluten meal. The AME value of RGM was 3035 and 3028 kcal/kg at 20 and 40% replacement levels of basal diet with a mean value of 3031 kcal/kg. However, with protease and multi-enzyme supplementation, a numerical increase of 37 and 35 kcal/kg of AME was observed, which was 1.22 and 1.15% more upon supplementation of protease and multi-enzyme, respectively. The proximate analysis revealed that rice gluten meal contains 92.30% dry matter which consists of 50% crude protein, 6.92% ether extract, 9.47% crude fibre, 21.54% nitrogen free extract and 4.37% ash. In vitro pepsin-pancreatin digestibility (IVPPD) of RGM was 81.50%. The total phosphorus content in the RGM was 0.78%, in which phytate content was 0.43% and non-phytate phosphorous was 0.35%, which is 44.87% of total phosphorous content. Hence, it can be concluded that RGM containing AME of 3031 kcal/kg, 50% crude protein with IVPP of 81.50% can prove to be a possible alternate feed source in the diet of poultry.